MAQTA wrtitting of Mah Laq Bai Chand in praise of Hazrat Ali - Dr. Muhammad Irfan Ahsan Pasha; Dr Rukhsana Bibi (Zaban-o-Adab, 2024)
Mah Laqa Bai famous by her pen name CHANDA holds the distinction to be the first female poet of Urdu literature with her alphabetical anthology called DIWAN. She was a cult of era.She had many talents including poetry. She led a prosperous life and never faced problems. She was poet of a sublimated and highly refined taste. She was a very much devoted follower of Hazrat Ali (the 4 th caliph of Islam). In her poetry she always praise for her spiritual mentor. Especially in every concluding couplet (called MAQTA) she describes her love and devotion for the bravest person of Islamic history. She presents a unique example of such poet in Urdu literature whose every Maqta is spared for a single theme. This article presents differentaspects of the Maqtas composed by Mah Laqa Bai Chanda which categorize them to different shades of her love and devotion for Hazrat Ali.